AB0694 Inertial Sensor for The Assessment of Cervical Range of Movement in Axial Spondyloarthritis. (15th July 2016) - Garrido-Castro, J.L.; Gonzalez-Navas, C.; Castro-Jurado, J.; Font-Ugalde, P.; Collantes-Estevez, E.
Abstract : Background: Axial Spondyloarthritis (AxSpA) affects mainly the spine reducing patient mobility including neck. Several tools have been used to evaluate range of motion in AxSpA, but these tools have problems of reliability and accuracy. Motion capture [1], has been recently developed and validated, however a dedicated laboratory of movement is needed. IMU sensors (Inertial Measurement Unit) are a new and cheap kind of technology that allows knowing 3D orientation. These sensors could provide equivalent results to motion capture, with lower requirements, although validation processes are needed. Objectives: To evaluate reliability of an inertial sensor IMU to assess cervical range of movement in patients with AxSpA. Methods: 7 male patients with AxSpA (age 55.9±11.9, time of evolution 14.37±10.74) were included. An IMU sensor (Shimmer3 © ) placed on the patient's forehead was used. 4 reflective markers were attached to the head using a band (one above the sensor, two over the tragus, and one in the occiput). To detect movement of the trunk, 4 more markers were used (2 over the shoulders, 10 cm below C7 and average distance between L4 and C7). 3D reconstruction was performed using the UCOTrack © system [1]. 3D orientation was obtained by the sensor and by the UCOTrack, both at 50 Hz. Patient made three bend movements (frontal, lateral and rotation). Measurements were repeated 5 minutes after. PRO questionnaires and structural damage (mSASSS) were also evaluated. Several statistical tests were performed to assess reliability of the sensor and its comparison with the Gold Standard. Results: Affectation level was widely spread among the study participants (BASDAI: 3.4±2.9; BASFI 4.2±3.9; BASMI 5.3±2.2; UCOASMI: 6.1±2.5; mSASSS: 39.9±22.4; cervical mSASSS: 17.9±8.8). Table shows the measurements in the three ranges of cervical motion and statistical parameters analyzed. Conclusions: Test/retest values were very similar, with excellent ICCs and low errors. Motion capture system detected some variations from 3° to 13° at the trunk. To place another IMU sensor at C7 to compensate it is recommended. Number of patients were very small and a model that analyzes the entire spine, not only the cervical part, must be developed. This pilot study shows that IMU sensor could be used, with results very similar to gold standard and with good reliability, improving metrology for AxSpA patients. References: Garrido-Castro JL, Medina-Carnicer R, Schiottis R, Galisteo AM, Collantes-Estevez E, Gonzalez-Navas C. Assessment of spinal mobility in ankylosing spondylitis using a video-based motion capture system. Man Ther. 2012 Oct;17(5):422–6. Disclosure of Interest: None declared